Sejarah peradilan Islam di Malaysia dan Brunei Darussalam - Roofi, Abdul (Maliki Interdisciplinary Journal, 2024)
Malaysia and Brunei Darussalam are two countries in the Southeast Asia region that have a form of kingdom with a monarchy system and Islamic law within it. If you look at their history, these two countries were former British colonies which later succeeded in becoming independent and developing to this day. In the judicial and legal system, they still maintain the laws adopted by the country that colonized them. However, one similarity that the two countries can maintain is that they still adhere to Islamic and customary law. So the article below will explain Islamic justice in Malaysia and Brunei Darussalam, from various points of view. By using literature methods through books and several previous articles, we can finally conclude that Islamic justice in Malaysia and Brunei Darussalam has existed for a long time, but since the arrival of the British, Islamic justice law applied in these two countries has begun to intervene. English in it. Even after independence, the laws abandoned by England still remained, but Islamic law which had been narrowed was expanded and developed by each of these countries.